1994
DOI: 10.1111/j.1365-2141.1994.tb04910.x
|View full text |Cite
|
Sign up to set email alerts
|

PCR assessment of bone marrow status in ‘isolated’extramedullary relapse of childhood B‐precursor acute lymphoblastic leukaemia

Abstract: Approximately one-third of first relapses of childhood ALL occur at an extramedullary site without morphological evidence of bone marrow disease. However, the high incidence of subsequent medullary relapse in these cases strongly suggests that leukaemia is present at submicroscopic levels at the time of 'isolated' relapse. PCR analysis of immunoglobulin heavy chain (IgH) and T-cell receptor (TCR) gene rearrangements now allows detection of leukaemia at levels as low as 0.001%. We have therefore used this techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Such a clinical course has been reported to be extremely uncommon after allogeneic bone marrow transplantation, 11 but relatively common in 'isolated' CNS relapse after chemotherapy in ALL. 13 On the other hand, our second case appeared to support the latter mechanism. After BMT, the marrow was the primary site of relapse.…”
Section: Discussionmentioning
confidence: 58%
“…Such a clinical course has been reported to be extremely uncommon after allogeneic bone marrow transplantation, 11 but relatively common in 'isolated' CNS relapse after chemotherapy in ALL. 13 On the other hand, our second case appeared to support the latter mechanism. After BMT, the marrow was the primary site of relapse.…”
Section: Discussionmentioning
confidence: 58%
“…Neale et al 22 identified molecular evidence of minimal residual disease in BM from four of six patients with T-cell ALL and isolated CNS recurrence. Goulden et al 23 identified minimal residual disease by polymerase chain reaction analysis in BM from 12 of 13 children with B-lineage ALL who had isolated extramedullary disease. 23 Using more intensive reinduction regimens has resulted in remarkably improved results.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the demonstration of low-level disease in hematologically normal bone marrows of patients with isolated extramedullary relapse [51][52][53] should be regarded as molecular relapse or disease left-over from an incomplete remission induction is semantic and may in part depend on the timeframe of events. Whatever the origin of disease, systemic therapy will be warranted in this situation.…”
Section: Molecular Relapsementioning
confidence: 99%